Boundedness and square integrability of solutions of nonlinear fourth-order differential equations with bounded delay - Korkmaz, E.; Tunç C. (Texas State University - San Marcos, 2017)
In this article, we give sufficient conditions for the boundedness, uniformly asymptotic stability and square integrability of the solutions to a fourth-order non-autonomous differential equation with bounded delay by using Lyapunov’s second method. © 2017 Texas State University.
Keywords: Boundedness; Delay differential equations; Fourth order; Lyapunov functional; Square integrability; Stability